Soulless the manga - REM ([Parasol protectorate series], 2012)
"Settling into her new life as the Lady Woolsey, Alexia finds her days quite challenging. Whether it is a regiment of supernatural soldiers camped out on her front lawn or the demands of being the Queen's 'muhjah,' there never seems to be a want of new hurdles to overcome. But when stories of supernaturals rendered normal by some unknown force begin cropping up, Alexia has a rather serious mystery on her hands. Can she root out the cause of this phenomenon, which smacks of some larger plot at work?"... P. [4] of cover